2011
DOI: 10.3109/08958378.2011.584080
|View full text |Cite
|
Sign up to set email alerts
|

Altered pulmonary defense system in lung injury induced by didecyldimethylammonium chloride in mice

Abstract: Didecyldimethylammonium chloride (DDAC), a representative dialkyl-quaternary ammonium compound (QAC), could contaminate working atmospheres when used in disinfectant operation and adversely affect human health. Furthermore, the development of bacteria resistant to DDAC might become public health concern. We postulated that DDAC instillation in the lungs alters pulmonary antioxidant and antimicrobial responses and increases susceptibility to systemic administration of a bacterial component lipopolysaccharide (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…[9], [11] Their manufacturers recommend their dilution, typically 5 mL of HD in 3 L of distilled water. PHMG and PGH are well-known disinfectants for the treatment of various medical conditions, and their use dates back to the late 19th century.…”
Section: Discussionmentioning
confidence: 99%
“…[9], [11] Their manufacturers recommend their dilution, typically 5 mL of HD in 3 L of distilled water. PHMG and PGH are well-known disinfectants for the treatment of various medical conditions, and their use dates back to the late 19th century.…”
Section: Discussionmentioning
confidence: 99%
“…2B). Despite the differences in material and experiment design, Ohnuma et al (2010Ohnuma et al ( , 2011 reported that decyldimethylammonium chloride (DDAC) which is used as a germicide causes lung fibrosis including change of BALF cells, level of LDH and TP concentration in BALF after intratracheal instillation. However, in histopathological examination, our results were not found to be treatment-related lesions in the lungs at higher exposure dose compared with DDAC study (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…DDAC is a broad-spectrum bactericidal and fungicidal biocide that exhibits antimicrobial activity against several pathogens such as Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa (Walsh et al 2003), Legionella pneumophilia (Skaliy et al 1980), Stachybotrys chartarum and enveloped and non-enveloped viruses (Argy et al 1999). It is used in several types of applications including: industrial processes, swimming pools and aquatic areas, wood treatment, healthcare and food handling and storage (Ohnuma et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Ohnuma et al (2011) examined the pulmonary defense system following a single intratracheal instillation of DDAC (60 and 150 μg/kg) in C57BL/6J mice. Those authors found that exposure to the high dose induced lung injury as early as 1-d post-exposure, as evidenced by increased lactate dehydrogenase (LDH) activity and protein concentrations in the bronchoalveolar (BAL) fluid.…”
Section: Introductionmentioning
confidence: 99%